1,3 Cyclohexanedione / Benzene-D6 - B.S. Hudson, Syracuse University, New York, USA (My University, 2004)
Inelastic Neutron Scattering spectrum of 1,3 Cyclohexanedione / Benzene-D6, C₆H₈₀₂ / C₆D₆, measured on the TOSCA instrument.
Keywords: TOSCA